2010
DOI: 10.1073/pnas.0913745107
|View full text |Cite
|
Sign up to set email alerts
|

Peptide antagonism as a mechanism for NK cell activation

Abstract: Inhibition of natural killer (NK) cells is mediated by MHC class I receptors including the killer cell Ig-like receptor (KIR). We demonstrate that HLA-C binding peptides can function as altered peptide ligands for KIR and antagonize the inhibition mediated by KIR2DL2/ KIR2DL3. Antagonistic peptides promote clustering of KIR at the interface of effector and target cells, but do not result in inhibition of NK cells. Our data show that, as for T cells, small changes in the peptide content of MHC class I can regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
187
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 148 publications
(208 citation statements)
references
References 41 publications
17
187
2
Order By: Relevance
“…Of note, however, the inhibitory effect of HLA-C ⁄ 03:04 + /HCV core peptide-pulsed target cells on NK cells requires a 100-1000-fold higher peptide concentration in in vitro assays than typically required for T cell stimulation. This is in line with other studies [16]. While the inhibitory effect on NK cells is detectable at 10 lM peptide concentration [7], T cell stimulation can often still be observed in the 0.01 to 0.1 lM range.…”
supporting
confidence: 93%
“…Of note, however, the inhibitory effect of HLA-C ⁄ 03:04 + /HCV core peptide-pulsed target cells on NK cells requires a 100-1000-fold higher peptide concentration in in vitro assays than typically required for T cell stimulation. This is in line with other studies [16]. While the inhibitory effect on NK cells is detectable at 10 lM peptide concentration [7], T cell stimulation can often still be observed in the 0.01 to 0.1 lM range.…”
supporting
confidence: 93%
“…The interactions of KIR2DL are further diversified by polymorphism within the subsets of C1‐bearing and C2‐bearing HLA allotypes 34, 103. The basis for these hierarchies may occur due to polymorphism at sites other than position 80, or the distinct repertoires of peptide presented by the different HLA‐C allotypes 106. An additional feature of HLA‐C polymorphism is the differential cell surface expression exhibited by individual allotypes,91 although how this variation impacts NK cell reactivity is yet to be fully defined.…”
Section: Kir Ligand Bindingmentioning
confidence: 99%
“…Peptides derived from a variety of viruses, including EBV, HIV, and CMV, are known to bind to HLA-E (24-26). The HIV p24 peptide residues 14-22 (HIVp24 [14][15][16][17][18][19][20][21][22] , AISPRTLNA) was identified by a motif-based approach, and in chronic HIV infection the up-regulation of HLA-E on CD4 + T cells results in increased inhibition of NKG2A + NK cells (25,30). The peptide SQAPLPCVL from EBV BZLF-1 protein residues 39-47 (EBVbzlf [39][40][41][42][43][44][45][46][47] ) also has been shown to bind to HLA-E (24).…”
Section: Hcv Corementioning
confidence: 99%
“…It has been shown that KIR + NK cells can be modulated by changes in the peptide bound by MHC class I, which confers additional functionality on the KIR system (16)(17)(18). In particular peptide antagonism is a potent mechanism for activating KIR + NK cells (19,20). The CD94-NKG2A receptor also is peptide selective, with receptor binding being particularly influenced by residues 5, 6, and 8 of the peptide bound by HLA-E (21-23).…”
mentioning
confidence: 99%